Weakly spin-dependent band structures of antiferromagnetic perovskite LaMO3 (M = Cr, Mn, Fe). (24th January 2018) - Okugawa, Takuya; Ohno, Kaoru; Noda, Yusuke; Nakamura, Shinichiro
Abstract: We investigate the spin-dependent electronic states of antiferromagnetic (AFM) lanthanum chromite (LaCrO3 ), lanthanum manganite (LaMnO3 ), and lanthanum ferrite (LaFeO3 ) using spin-polarized first-principles density functional theory with Hubbard U correction. The band structures are calculated for 15 types of their different AFM structures. It is verified for these structures that there is a very simple rule to identify which wave number k exhibits spin splitting or degeneracy in the band structure. This rule uses the symmetry operations that map the up-spin atoms onto the down-spin atoms. The resulting spin splitting is very small for the most stable spin configuration of the most stable experimental structure. We discuss a plausible benefit of this characteristic, i.e. the direction-independence of the spin current, in electrode applications.